2005
DOI: 10.1002/chem.200500534
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on a Prion's Helix II Domain: Copper(II) and Membrane Interactions with PrP180–193 and Its Analogues

Abstract: An abnormal interaction between copper and the prion protein is believed to play a pivotal role in the pathogenesis of prion diseases. Copper binding has been mainly attributed to the N-terminal domain of the prion protein, but this hypothesis has recently been challenged in some papers which suggest that the C-terminal domain might also compete for metal anchoring. In particular, the segment corresponding to the helix II region of the prion protein, namely PrP180-193, has been shown both to bind copper and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 52 publications
(73 reference statements)
9
35
0
Order By: Relevance
“…Our previous studies led to the same conclusions and the high copper(II) binding ability of His96, His111 and even His187 residues was unambiguously demonstrated in the small fragments of the protein [22][23][24]. The results obtained for the 31-and 39-mer peptide fragments, namely HuPrP(84-114) and HuPrP(76-114), made it possible to compare the metal binding affinities of histidyl residues inside and outside the octarepeat domain.…”
Section: Introductionsupporting
confidence: 72%
“…Our previous studies led to the same conclusions and the high copper(II) binding ability of His96, His111 and even His187 residues was unambiguously demonstrated in the small fragments of the protein [22][23][24]. The results obtained for the 31-and 39-mer peptide fragments, namely HuPrP(84-114) and HuPrP(76-114), made it possible to compare the metal binding affinities of histidyl residues inside and outside the octarepeat domain.…”
Section: Introductionsupporting
confidence: 72%
“…[67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated. A comparison of the thermodynamic stabilities of the histidinecontaining fragments revealed that the peptides that encompass the amino acid sequences outside the octarepeat domain are even more efficient chelators of copper(II) than the single octarepeat fragments.…”
Section: Introductionsupporting
confidence: 71%
“…Figure 11 shows the distribution diagram obtained for copper(II) complexes with Dpl-A C H T U N G T R E N N U N G (122-139) and the peptide fragment PrP C A C H T U N G T R E N N U N G (184-188) blocked at the C and N terminus, which has been shown to be a reliable model for the interaction between metals and the helix II domain of prion. [38] The diagram shows that at acidic pH …”
Section: Wwwchemeurjorgmentioning
confidence: 97%